Paisagem, patrimônio e dinâmica turística de Peirópolis, Uberaba-MG - Fernandes, Helier Gomes Muniz (2023)
The act of traveling follows the civilization, from American indigenous populations to eastern populations. With the post-industrial era, the activity of traveling presented the first steps for tourism to emerge and spread around the world. Tourism is a social and economic practice that produces geographic space and has undergone several transformations. As a starting point for the development of tourist activity, in this work we will emphasize the paleontological heritage, which is inserted in the neighborhood of Peirópolis, in Uberaba, Minas Gerais. The main objective of this work is to understand the tourist dynamics of Peirópolis from the point of view of the Geography of Tourism. For the specific objectives it is necessary: a) to characterize the role of the landscape in the composition of the tourist territory of Peirópolis; b) understand the formation and organization of this tourist territory; c) identify which socioeconomic and environmental dynamics make the territory dynamic as a scientific-cultural tourist destination. A literature review was carried out to discuss important concepts for the theoretical basis, document analysis on sites such as the Ministry of Tourism, Uberaba City Hall, among others. Field collections were carried out in the area where the Center and Museum in Peirópolis are located. Then, the data collected in the field were confronted with a literary review and document analysis. Due to the survey being carried out within a pandemic period, it was not possible to interview tourists. Tourism in Peirópolis is an important transforming factor for that geographic space and landscape, which has a characteristic of dynamic social construction. With the pandemic, tourism was destroyed in many already consolidated destinations, a detouristification occurred in previously touristified landscapes. Even with the resumption of tourism, there was a regression and tourism is still reinventing itself. Peirópolis has the structure to receive a small number of people when compared to large tourist centers. Its fossil finds were the originator for landscape modification. This is linked to the formation and organization of the territory. Paleontology brings curiosity to the public, which is guaranteed by the complex. The public is interested in what Peirópolis offers, making it viable as a scientific-cultural tourist destination. This leads to the social and economic development of the residents of the neighborhood, which contributes to the candidacy of Unesco's chancellor geopark, which helps in the process of expansion and consolidation of tourism in the city of Uberaba and for the tourist circuits that the city is part of. The obstacles created during the Covid-19 pandemic may cause effects for reflections within tourism. In addition, carrying out studies on its action and consequences can lead not only to a plan, but to public policies that can cover or be more efficient within the segment in emergency situations such as those experienced recently.